Host ESCRT machinery orchestrates the assembly of tomato spotted wilt virus ribonucleoproteins - Kikyo Watanabe; Chihiro Oda-Yamamizo; Kazuhiro Ishibashi (Proceedings of the National Academy of Sciences, 2026)
The genomic RNA of negative-strand RNA viruses is encapsidated by nucleocapsid proteins and associates with RNA polymerase to form a ribonucleoprotein (RNP) complex. Lacking both a 5’ cap and a 3’ poly (A) tail, viral RNAs are highly unstable and prone to degradation by cellular nucleases. Therefore, newly synthesized genomic and complementary-strand RNAs must be rapidly protected through RNP formation. However, the molecular mechanisms governing RNP assembly in cytoplasm-replicating negative-strand RNA viruses remain largely unknown. Here, we screened a yeast knockout library and isolated mutants in several components of the endosomal sorting complexes required for transport (ESCRT) genes that affected RNA replication of tomato spotted wilt virus (TSWV). In wild-type (WT) yeast cells, TSWV nucleocapsid (N) and RNA polymerase (L) proteins colocalize at the trans-Golgi network (TGN) in a replicon-RNA-dependent manner, suggesting that TSWV RNPs accumulate at the TGN. However, in the snf7 Δ, bro1 Δ, and doa4 Δ mutant cells, N localization to TGN and RNP formation were impaired. Another RNA replication-defective mutant, vps36 Δ, showed normal N localization, and SNF7, BRO1, and DOA4 were recruited to the TGN by TSWV N or L proteins, implying that the ESCRT components have additional roles in TSWV RNA replication beyond facilitating N transport. These findings suggest that ESCRT components play multifaceted roles in TSWV RNA replication, including the intracellular transport of N to the TGN—where RNA replication takes place—thereby ensuring accurate and efficient RNP assembly.